Effect of non‐Saccharomyces yeast strains on 3‐isobutyl‐2‐methoxypyrazine concentration and aroma properties in Sauvignon Blanc wines during fermentation. (1st August 2022) - Li, J.‐C.; Wilkinson, K.L.; Ford, C.M.; Jiranek, V.
Abstract: Background and Aims: 3‐Isobutyl‐2‐methoxypyrazine (IBMP) is a compound whose aroma is reminiscent of green capsicum and is found in many winegrape cultivars, such as Cabernet Sauvignon and Sauvignon Blanc. A high concentration in grapes can lead to excessive greenness in the resulting wine products, thus reducing quality. This study sought to determine the impact of using non‐ Saccharomyces yeast during fermentation on the concentration and perception of IBMP in wines. Methods and Results: As a potential postharvest remediation strategy, 11 strains of non‐ Saccharomyces were evaluated through fermentation of juices containing IBMP. Wines fermented with Kazachstania servazzii, Metschnikowia pulcherrima, K. aerobia, Hanseniaspora uvarum, Meyerozyma guillermondii and Candida krusei were rated with a higher level of fruitiness and less greenness in sensory analysis, even though no significant difference was observed amongst yeast treatments for IBMP concentration. Conclusions: In mixed fermentation, in which Saccharomyces cerevisiae yeast strain EC1118 was sequentially inoculated, several non‐ Saccharomyces yeast strains differentially masked the perception of IBMP. Significance of the Study: The selective use of non‐ Saccharomyces yeast may be a strategy for modulating the excessive perception of greenness in wines derived from grapes containing a high concentration of IBMP.